1996
DOI: 10.1046/j.1471-4159.1996.66010330.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Immunocytochemical Localization of Neurotrophin‐3 in the Brain and Peripheral Tissues of Rats

Abstract: The tissue distribution of neurotrophin‐3 (NT‐3) was investigated in rats at 1 month of age using a newly established, sensitive two‐site enzyme immunoassay system for NT‐3, as well as the immunocytochemical localization of this protein. The immunoassay for NT‐3 enabled us to quantify NT‐3 at levels > 3 pg per assay. In the rat brain, NT‐3 was detectable only in the olfactory bulb (0.54 ng/g wet weight), cerebellum (0.71 ng/g), septum (0.91 ng/g), and hippocampus (6.3 ng/g). By contrast, NT‐3 was widely distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 0 publications
5
63
0
Order By: Relevance
“…In general, our results correlate well with previous in situ studies localizing NT-3 mRNA production in the rat (Ernfors et al, 1990a,b;Maisonpierre et al, 1990;Friedman et al, 1991;Lauterborn et al, 1994) and with immunocytochemical studies (Zhou and Rush, 1994;Söder-ström and Ebendal, 1995;Katoh-Semba et al, 1996Friedman et al, 1998). The major differences are that we detect X-gal staining in embryonic cortical cells and dentate gyrus precursors, and in young and aged adult cortices.…”
Section: Results Overviewsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, our results correlate well with previous in situ studies localizing NT-3 mRNA production in the rat (Ernfors et al, 1990a,b;Maisonpierre et al, 1990;Friedman et al, 1991;Lauterborn et al, 1994) and with immunocytochemical studies (Zhou and Rush, 1994;Söder-ström and Ebendal, 1995;Katoh-Semba et al, 1996Friedman et al, 1998). The major differences are that we detect X-gal staining in embryonic cortical cells and dentate gyrus precursors, and in young and aged adult cortices.…”
Section: Results Overviewsupporting
confidence: 92%
“…However, more recently, the distribution of NT-3 protein in the rat has been described using specific anti-NT-3 antibodies in enzyme immunoassays (Murase et al, 1994;Söderström and Ebendal, 1995) and in immunocytochemical studies (Zhou and Rush, 1994;Katoh-Semba et al, 1996;Friedman et al, 1998). These studies report the presence of NT-3 in the islands of Calleja, olfactory primary cortex, septum (including the diagonal bands of Broca), amygdala, hippocampus, hypothalamus, bed nuclei of the stria terminalis, cerebellum, mesencephalic trigeminal nuclei, and motor neurons in the brainstem and spinal cord (Zhou and Rush, 1994;Söderström and Ebendal, 1995;Katoh-Semba et al, 1996;Friedman et al, 1998). There is partial agreement between the in situ hybridization studies of NT-3 expression and immunocytochemical detection of in that the most prevalent expression is seen in the hippocampus and cerebellum.…”
mentioning
confidence: 99%
“…Guinea pig polyclonal anti-CAPS2 antibody and rabbit polyclonal anti-CAPS1 antibody (Sadakata et al, 2004) were used for the immunohistochemical analysis (used at dilution of 1:10,000 and 1:5000, respectively). Rabbit anti-NT-3 (Katoh-Semba et al, 1996), anti-BDNF (Katoh-Semba et al, 1997), and anti-phosphorylated Trk antibodies (pTrk) (Tyr490; catalog #9141; Cell Signaling Technology, Beverly, MA) were used for the immunohistochemical analysis (used at dilution of 1:150, 1:100, and 1:10, respectively). Mouse monoclonal anti-calbindin D-28K (C9848; Sigma, St. Louis, MO), anti-microtubule-associated protein MAP2(2a ϩ 2b) (M1406; Sigma), and anti-vesicular glutamate transporter (VGLUT2) (MAB5504; Millipore, Temecula, CA) antibodies were used for immunohistochemistry and immunocytochemistry (used at dilution of 1:500, 1:1000, 1:5000, and 1:4000, respectively).…”
Section: Caps2 Knock-out Micementioning
confidence: 99%
“…On the other hand, reverse transcription polymerase chain reaction (RT-PCR) on human liver specimens showed abundant NT-3 transcription and trace levels of Trk-B transcription. 11 Immunohistochemistry for NT-3 showed reactivity in all parenchymal cells of the liver, according to Zhou and Rush, 12 and reactivity in "liver cells" according to Kato-Sembah et al 13 Lomen-Hoerth and Shooter 14 were able to show a low level of p75 transcription in liver, by means of RNase protection assay, but were not able to show any Trk-A or Trk-B transcription. Koizumi et al 15 showed reactivity to Trk-A antibodies in hepatocellular carcinoma, but not in surrounding normal liver parenchyma.…”
mentioning
confidence: 94%